Analysis of Students Critical Thinking Skills of 5th Grade in Mathematics Learning - Purwati, Puji; Sumardi, Sumardi; Minsih, Minsih; Prastiwi, Yeny; Rahmawati, Laili Etika (Universitas Muhammadiyah Mataram, 2022)
Critical thinking skills are skills that are needed in the face of rapid technological development. The level of critical thinking skills in mathematics learning needs to be researched to analyze the extent to which the culture of critical thinking skills has been carried out. This study aims to describe the level of critical thinking skills of 5th graders in mathematics learning. The type of research used is descriptive research with a qualitative approach. The subjects of this study were grade 5 students at SD Negeri 1 Miricinde, as many as 15 students. This study uses a written test in the form of a description question. The data obtained are then analyzed by correcting students' answers. Critical thinking skill instruments contain aspects of critical thinking skills developed by including aspects: providing explanations simply, determining the basis of decision making, concluding, providing further explanations, estimating and combining. The results of the data analysis obtained, 26.7% of students have low critical thinking skills, 46.7% of students have sufficient critical thinking skills, 20% of students have high critical thinking skills, and 6.7% of students have very high critical thinking skills. So it can be concluded that the 5th grade students of Miricinde State Elementary School 1 have a sufficient level of category critical thinking skills.